Relationship of Coping Style and Self-efficacy with Satisfaction of Rehabilitation Practitioner Students with their Clinical Experiences - Yaser Rezapour-Mirsaleh; Kianoush A'bdi; Mahdi Rahgozar; Shahnaz Reyhani-Kivi (University of Social Welfare and Rehabilitation Sciences, 2011)
Objective: The purpose of present study was to investigate the Relationship of coping styles and self-efficacy with satisfaction of physical therapy, occupational therapy and speech therapy rehabilitation practitioner students with their clinical experience as a therapist. Materials & Methods: The study sample includes 318 rehabilitation practitioner students witch selected with proportional stratified sampling model. Rehabilitation Practitioner students includes 140 physical therapy students, 97 occupational therapy students, and 81 speech therapy students. Data were collected through Ways of coping questionnaire, general self-efficacy and clinical experience satisfaction questionnaire, and then analyzed with the help of correlation and multiple regression analysis. Results: Results show that satisfaction with clinical experience was positively and significantly correlated with positive reappraisal coping in all students in three branches.(P<0/05). Seeking social support and planful problem-solving coping was positively and significantly correlated with satisfaction with clinical experience in physical therapy and occupational therapy students. (P<0/05). Also, satisfaction with clinical experience in all students was positively and significantly correlated with self-efficacy. (P<0/001). Results show that self efficacy, in all students in three branches, and has more portion in predict of satisfaction with clinical experiences. Conclusions: The findings show that coping styles and self-efficacy positively and significantly predict of satisfaction with clinical experiences in three branches.